Demonstration of the cold sintering process study for the densification and grain growth of ZnO ceramics. Issue 2 (27th October 2016) - Funahashi, Shuichi; Guo, Jing; Guo, Hanzheng; Wang, Ke; Baker, Amanda L.; Shiratsuyu, Kosuke; Randall, Clive A.
Abstract: With the cold sintering process (CSP), it was found that adding acetic acid to an aqueous solution dramatically changed both the densities and the grain microstructures of the ZnO ceramics. Bulk densities >90% theoretical were realized below 100°C, and the average conductivity of CSP samples at around 300°C was similar to samples conventionally sintered at 1400°C. Frequently, ZnO is also used as a model ceramic system for fundamental studies for sintering. By the same procedure as the grain growth of the conventional sintering, the kinetic grain growth exponent of the CSP samples was determined as N =3, and the calculated activated energy of grain growth was 43 kJ/mol, which is much lower than that reported using conventional sintering. The evidence for grain growth under the CSP is important as it indicates that there is a genuine sintering process being activated at these low temperatures and it is beyond a pressurized densification process.